Influence of concomitant androgen deprivation therapy and its duration for salvage radiation after radical prostatectomy: a systematic review and network meta-analysis according to published data - Le, Quynh Chi; Siech, Carolin; Hoeh, Benedikt; Saad, Fred; Preisser, Felix; Tilki, Derya; Graefen, Markus; Maurer, Tobias; Kriegmair, Maximilian; Karakiewicz, Pierre I.; Chun, Felix K. H.; Mandel, Philipp; et al. (European urology oncology, 2025)
Background and objective - Recently published data comparing the impact and duration of androgen deprivation therapy (ADT) on metastasis-free survival (MFS), progression-free survival (PFS), and overall survival (OS) in patients undergoing salvage radiation therapy (sRT) after radical prostatectomy have not been compared directly; this study aims to address this knowledge gap. - Methods - We performed a systematic review and network meta-analysis (NMA) on MFS, PFS, and OS using data from the RADICALS-HD, NRG/RTOG 9601, RTOG 0534, and GETUG-AFU 16 trials, as well as three trials from the ARTISTIC meta-analysis (GETUG-AFU 17, RADICALS-RT, and RAVES) on adjuvant versus salvage radiotherapy. The primary outcome was MFS; the secondary outcomes were PFS and OS. Stratification was made according to ADT duration (ADT for 24 mo vs ADT for 6 mo vs no ADT). Subgroup analyses addressed high-risk cohorts with Gleason score ≥8 and positive surgical margins (PSMs). - Key findings and limitations - Data from 3710 prostate cancer patients were analyzed. Addition of ADT to sRT improved MFS and PFS significantly, regardless of the duration, but had no significant effect on OS. Hazard ratios (HRs) for ADT for 24 mo versus no ADT were 0.70 (confidence interval [CI] 0.53-0.92) for MFS, 0.51 (CI 0.43-0.61) for PFS, and 0.80 (CI 0.63-1.01) for OS; for ADT for 6 mo versus no ADT, the respective HRs were 0.79 (CI 0.65-0.97), 0.57 (CI 0.48-0.67), and 0.93 (CI 0.72-1.20). In subgroup analyses, ADT for 24 mo was ranked highest for MFS in patients with PSMs and Gleason score ≥8. - Conclusions and clinical implications - The NMA supports the addition of ADT to sRT, particularly a 24-mo duration, which provides the best MFS and PFS outcomes. While OS did not improve significantly, patients with Gleason score ≥8 or PSMs also benefit from prolonged ADT.
Online verfügbar: 29. Mai 2025, Artikelversion: 26. November 2025
Gesehen am 18.02.2026